PERBANDINGAN PERTUMBUHAN KERANG DARAH (Anadara granosa) DI PERAIRAN MOTADIKIN DAN KLETEK KABUPATEN MALAKA - Anar, Maria Frumensia Helmayati; Santoso, Priyo; Jasmanindar, Yudiana (Nusa Cendana University, 2025)
The research was carried out for 3 months starting from April to July 2024, at two different locations, namely Motadikin waters and Kletek waters, Central Malaka District, Malacca Regency. The parameters observed in this study were growth in absolute weight, absolute length, survival and water quality. Comparison of the growth and survival of blood cockles can be seen that the highest growth in absolute weight and absolute length is found in Kletek waters and the lowest in Motadikin waters.